1995
DOI: 10.1007/bf02035152
|View full text |Cite
|
Sign up to set email alerts
|

Aggregation pheromone of coconut rhinoceros beetle,Oryctes rhinoceros (L.) (coleoptera: Scarabaeidae)

Abstract: Abstract-Male coconut rhinoceros beetles, Orycres rhinoceros (L.), produce three sex-specific compounds, ethyl 4-methyloctanoate, ethyl 4-methylheptanoate, and 4-methyloctanoic acid, the first of which is an aggregation pheromone. Synthesis of these compounds involving conjugate addition of organocuprates to ethyl acrylate is reported. In field trapping experiments, (4S)-ethyl 4-methyloctanoate and the racemic mixture were equally attractive and 10 times more effective in attracting beetles than ethyl chrysant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
66
4
7

Year Published

1999
1999
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(79 citation statements)
references
References 52 publications
2
66
4
7
Order By: Relevance
“…The aggregation pheromone, i.e. attracting both males and females, ethyl 4-methyloctanoate (E 4-MO), which is produced by O. rhinoceros males, leads to substantial captures of adults, both males and females (Hallett et al, 1995). A dose/response effect was found: the higher the dose, the larger the captures.…”
Section: The Beetle Disillusionmentioning
confidence: 99%
“…The aggregation pheromone, i.e. attracting both males and females, ethyl 4-methyloctanoate (E 4-MO), which is produced by O. rhinoceros males, leads to substantial captures of adults, both males and females (Hallett et al, 1995). A dose/response effect was found: the higher the dose, the larger the captures.…”
Section: The Beetle Disillusionmentioning
confidence: 99%
“…Menurut Winarno (1992) (Hallett et al, 1995;Morin et al, 1996). Metode sintesis dari feromon agregasi O. rhinoceros L. telah dikembangkan (Bedford, 2014) (Widyanto et al, 2014).…”
Section: Pendahuluanunclassified
“…Kondisi optimum suhu dan kelembaban untuk perkembangan dan aktivitas serangga adalah 25℃ dan kelembaban 70-89% (Jumar, 2000). (Hallett et al, 1995;Morin et al, 1996). Campuran (blend) dari feromon agregasi sintetik inilah yang diduga menyebabkan imago betina lebih banyak terperangkap, karena imago betina mengenali molekul-molekul dari feromon agregasi sintetik ini dan meresponsnya dengan mencari asal dari bau feromon tersebut.…”
Section: Pengamatanunclassified
“…A few other chrysanthemumates, geraniol, curlure (4-(p-hydroxyphenyl)-2-butanone acetate), siglure (1-methylpropyl trans-6-methyl-3-cyclohexane), 2,5-dimethyl-2,4-hexadiene, isopentyl and phenethyl butyrate, trans-2-hexenal, butyl and pentyl hexanoate were much less attractive in field experiments (BARBER et al 1971, VANDERMEER et al 1979). Pheromones of Oryctini are known only from the above-mentioned two species: a male aggregation pheromone, ethyl-4-methyloctanoate, and a further attractive substance, ethyl-4-methylheptanoate (GRIES et al 1994, HALLETT et al 1995, MORIN et al 1996, RENOU et al 1998. Recently, RENOU et al (1998) found olfactory receptor cells in the antennae of female 0. rhinoceros for ethyl-4-methyloctanoate, phenyl ethanol, phenol, phellandrene, isoamyl acetate, Z3-hexenol, and ethyl chrysanthemumate.…”
Section: Quinones or Ethanol?mentioning
confidence: 99%